Development of Instrumen Eksplorasi Karier Anne Roe (IEKAR) for Junior High School Students - Suwidagdho, Dhanang; Purwanta, Edi (Jurnal Kajian Bimbingan dan Konseling, 2022)
This study aims to develop a career exploration instrument based on Anne Roe’s classification to help junior high school students explore their career options. The development method uses the Syaiffudin Azwar instrument development model with 8 stages, namely the identification of measuring objectives; measuring domain restrictions; operationalization of aspects; writing and reviewing items; language test; field tests; item selection and; final compilation. The field test was carried out on 306 junior high school students in the Godean area, Yogyakarta. The results of the CFA test show that all instrument items that make up the 8 career groups obtained fit results based on the p-value indicators of 0.257, RMSEA 0.15, GFI 0.87, AGFI 0.86, and CFI 1.00. CFASO test results obtained p-value 0.257 greater than 0.05 and RMSEA value 0.015 less than 0.05. In addition, the results of multidimensional reliability testing showed a score of 0.87 greater than 0.70. These findings indicate a valid and reliable instrument to help explore the careers of junior high school students.